Language-specific factors in first language acquisition : the expression of motion events in French and German - Harr, Anne-Katharina (Studies on language acquisition, 2012)
A growing number of studies have begun to examine the influence of language-specific factors on language acquisition. During language acquisition, German children from six years on use structures that are similar to those of adults in their language group and also encode all semantic components from an early age. In striking contrast, French children up to ten years have difficulties producing some of the complex structures that are necessary for the simultaneous expression of several semantic components. Nonetheless, in addition to these striking cross-linguistic differences, the results of t.